2019
DOI: 10.35654/ijnhs.v2i3.213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Promotion Using Leaflets and Audio-Visual on Improving Knowledge and Attitude Toward the Danger of Hiv/Aids Among Adolescents

Abstract: HIV/AIDS in adolescents cannot be separated from globalization development, which causes their current social changes and negative lifestyle such as pre-marriage sex, keeping on changing sex partners, and drug abuse. Promotional action should be done to prevent from HIV/ASIDS in adolescents by using leaflet and audio-visual media, which provide information and education about the danger of HIV/AIDS so that they will have good knowledge and positive attitude. The research problem was how about the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…This research is supported (Djannah et al, 2020) that health education through audiovisual media increased adolescent knowledge about reproductive health as indicated by the results the average score of respondents before and before the intervention increased significantly. This is line with study (Siregar et al, 2019) showed there are differences in knowledge before and after being given intervention in adolescent with leaflet and audiovisual media about the dangers of HIV / AIDS. Loewenstein, G., & Furstenberg, F. (1991) states that the forms of sexual behavior in adolescents generally start from the less intimate level to the most intimate or have sexual intercourse carried out by holding hands, shoulders, kissing lips while hugging, embracing , attach the genitals (petting sex) to finally have sexual intercourse (Winarso et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This research is supported (Djannah et al, 2020) that health education through audiovisual media increased adolescent knowledge about reproductive health as indicated by the results the average score of respondents before and before the intervention increased significantly. This is line with study (Siregar et al, 2019) showed there are differences in knowledge before and after being given intervention in adolescent with leaflet and audiovisual media about the dangers of HIV / AIDS. Loewenstein, G., & Furstenberg, F. (1991) states that the forms of sexual behavior in adolescents generally start from the less intimate level to the most intimate or have sexual intercourse carried out by holding hands, shoulders, kissing lips while hugging, embracing , attach the genitals (petting sex) to finally have sexual intercourse (Winarso et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…This correspondence to reaserch conducted by A scoping review from (Condran et al, 2017) suggests that the results of this study support the use of social media in sexual health promotion interventions, especially promoting environmental, individual behavior change. Besides that, Supoorted study show the results of research on adolescents, the average difference in attitude ranking is 0.00 before the intervention and the average rank is 7.00 after being given an intervention with leaflets and audiovisual media about the dangers of HIV/AIDS (p = 0.001 or p < 0.005) (Siregar et al, 2019) In the control group, the research also shows that there is a significant difference in the level of knowledge before and after being given Peer Education. According to Ghasemi et al, (2019) The benefit of peer-to-peer approach is that they imitate each other peer group, easy transfer of information between colleagues, especially if it is supported by a good peer understanding of social and cultural target group, environmental characteristics, and active peer participation in all stages of planning, implementation and evaluation.…”
Section: Discussionmentioning
confidence: 85%
“…As HIV-related social stigma can adversely impact many aspects of PLWH life including their access to healthcare, well-being, social support, etc., studies with the general population are needed to reflect the social aspects of HIV-related stigma. Young women [22], African American and Latino men [42], households [25,43], workers [44], students [45,46], adolescents [47], and LGBT communities [48] were other groups that have been investigated. While social stigma is an important type of HIV stigma addressed by many studies, other types, like internalized stigma, are not fully addressed.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…The informants recommended both printed (leaflets, brochures, booklets, posters, banners, pamphlets, and stickers) and electronic media (video and social media) as the tools. The previous research has also stated that leaflets, audio-visuals, brochures, booklets, posters, banners, and social media were effectively used in various fields of health promotion [42], [43], [44], [45], [46]. However, care must be taken in producing and conveying antistigma messages because psychological reactance was identified as one of the obstacles.…”
Section: Discussionmentioning
confidence: 99%